Epidemiologic characteristics of outbreaks of three norovirus genotypes (GII.2, GII.17 and GII.4 Sydney) in Guangzhou, China, from 2012 to 2018. (2019) - Wang, H.; Wang, D. H.; Chen, C.; Lu, Y.; Li, M. X.; Li, T. G.; Zhang, Z. B.; Yang, Z. C.
Abstract: To compare the epidemiologic features (e.g. settings and transmission mode) and patient clinical characteristics associated with outbreaks of different norovirus (Nov) strains, we retrospectively analysed data of Nov outbreaks occurring in Guangzhou, China from 2012 to 2018. The results suggested that outbreaks of Nov GII.2, GII.17 and GII.4 Sydney exhibited different outbreak settings, transmission modes and symptoms. GII.2 outbreaks mainly occurred in kindergartens, elementary and high schools and were transmitted mainly through person-to-person contact. By contrast, GII.4 Sydney outbreaks frequently occurred in colleges and were primarily associated with foodborne transmission. Cases from GII.2 and GII.17 outbreaks reported vomiting more frequently than those from outbreaks associated with GII.4 Sydney.